PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PROYEK BERBANTUAN MEDIA KOMIK DIGITAL PADA PEMBELAJARAN MENULIS TEKS CERITA PENDEK - Suhendar, - (2020)
In learning Indonesian, there are still problems with the difficulties of students expressing and developing ideas in written form and students still lacking in appreciating literary works and creating a pleasant atmosphere for learning literature. This study aims to improve students 'skills in producing short story texts and foster students' motivation in learning to write short stories by utilizing a variety of learning models and media. When studied more deeply, the problem that is often found is the difficulty of students expressing and developing their ideas and ideas. In addition, students are only accustomed to writing when asked by the teacher or not on their own initiative so that students' abilities are not honed. Based on this, it is necessary to have a variety of models and media that use technology to support successful learning. The project-based learning model assisted by digital comic media is a model that suits the characteristics of vocational school students, because this model directs students to play an active and creative role so that learning objectives can be achieved. Digital comics try to give different nuances to the model through the imagination and hands-on experiences that students have. The method used in this research is research and development (R&D). The results showed a positive impact on improving student learning outcomes seen from the teacher's or student's response very well when this model was applied in vocational schools in Bandung Regency. It can be said that the project-based learning model assisted by digital comic media is effective in improving students' short story text writing skills. This shows that the project-based learning model assisted by digital comic media can be used or applied as a means of supporting learning for teachers in delivering learning materials so that an effective learning nuance is created. Keywords : Project-Based Learning Model, Comic Media, Writing Short Story Texts